Derecho a la resistencia en el constitucionalismo ecuatoriano: ambigüedad y estabilidad democrática - Muñoz Lucio, Angelica Brigitt (2025)
The right to resistance is crucial for protecting fundamental rights since it allows individuals and groups to oppose actions or omissions of public power that violate constitutional rights. Although the Ecuadorian Constitution recognizes this right, its scope needs to be broadened and clarified, posing challenges in its interpretation and application. This study aims to analyze the right to resistance in the nstitutional framework of Ecuador, exploring its ambiguity and its impact on democratic stability. A methodological approach will include a theoretical framework that addresses definitions, characteristics, and normative analysis. In addition, surveys will be applied to expert judges in constitutional law, prosecutors, and a former indigenous leader and president of the Confederation of Indigenous Nationalities of Ecuador, who meet inclusion criteria based on their deep knowledge of the subject. The information obtained will be crucial to understanding the reality of this right, which, although constitutionally recognized, lacks specific legislation that delimits the conduct permitted under its protection. Regulatory ambiguity can lead to subjective interpretations that, without clear criteria of legality and proportionality, could justify violent or criminal acts. Therefore, it is essential to establish an adequate procedure for exercising the right to resistance, guaranteeing that it is used when rights enshrined in the Constitution are violated. The lack of clarity around the limits of this right has significant implications for democratic stability in Ecuador.